Paul V. Stock, Michael Carolan & Christopher Rosin (eds.), Food Utopias: Reimagining citizenship, ethics and community, New York: Routledge, 2015. - Ramalhete Gomes, Miguel (Cadernos de Literatura Comparada (teste), 2017)
.